Analysis Application Learning Model for Pancasila and Citizenship Education (PPKN) Subjects for Students Class IV Elementary School in Langkat, North Sumatera - Wulandari, Yuni (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Article This aims to analyze the application of learning models to the eye Pancasila and Citizenship Education ( PPKN ) lessons for student Class IV Elementary School in Langkat, North Sumatra. In context, this is challenge main is How to implement an effective and interesting learning model for the student. Many challenges faced cover the lack of facility supporter learning, methods of monotonous teaching, as well lack of teachers ' understanding of innovative and effective learning models. Through analysis This is expected can know the weaknesses and strengths of existing learning models, and searching the solution best For increasing quality learning PPKN for students Class IV Elementary School in Langkat, North Sumatra.